Staged tricortical bone graft with internal fixation in complex distal humerus fracture: a prospective study - Maheshwari, Prince; Pushprajan; Ojha, Ankur; Singh, Ajit; Kumar, Satyam (International Journal of Research in Orthopaedics, 2024)
Background: Complex distal humerus fractures present a significant challenge in orthopaedic surgery. This study evaluates the efficacy of staged tricortical bone graft combined with internal fixation in these fractures. Methods: A prospective study involving 50 patients with complex distal humerus fractures treated with staged tricortical bone graft and internal fixation was conducted. The primary outcomes measured were radiographic union and functional recovery using DASH and MEPS scores over a 12-month period. Results: Radiographic union was achieved in 100% of patients at 12 months. Significant improvements in functional outcomes were noted, with DASH and MEPS scores improving from 75.3 and 55.4 at baseline to 20.1 and 95.0, respectively, at 12 months (p<0.001). The complication rate included an 8% incidence of postoperative infection and a 6% rate of non-union. Subgroup analysis indicated slightly better outcomes in patients under 50 years. Conclusion: Staged tricortical bone graft combined with internal fixation demonstrates high efficacy in treating complex distal humerus fractures, offering high union rates and significant functional improvements. While the results are promising, further research is needed for broader validation.